Synergism in Nitrogen-A nd Phosphorus-Based Flame Retardants - (:unkn) unknown (American Chemical Society, 2021)
Polyurethane foams (PUFs) are polymer materials with extremely flammable properties. In the framework of the legal regulations made for the protection of life and property safety, it is necessary to use flame retardants(FRs)in polymers.Toxic gases are formed as a result of the combustion of most of the halogenated FRs, and the use of halogenated FRs is restricted owing to the damages they cause to human health and nature. Therefore, the development of halogen-free FRs draws attention to replacements for the halogenated ones. Moreover, the inclusion of various halogen-free FRs can provide better flame retardancy to PUFs. The use of FR combinations can lead to synergistic effects, and FR systems containing multiple FR elements-such as phosphorus-nitrogen, phosphorus-silicon, and phosphorus-nitrogen-silicon systems-have been developed. Because of the good synergy between phosphorus and nitrogen, the subject of many studies has been phosphorus/nitrogen (P/N)synergy and flame retardancy.Using synergistic systems is the most effective way to reduce the halogenated FR content in polymeric materials because P/N-containing FR systems provide good thermal stability, low toxicity,and low smoke generation. In this chapter, first, information about PUFs is given briefly; next, the types and properties of PUFs are mentioned. Then, the FR mechanisms used in PUFs and P/N FRs are investigated, the effects of FRs on the morphology and mechanical properties of PUFs are explained,and, finally, the thermal degradation behavior of PUFs and the tests used in thermal degradation are clarified. © 2021 American Chemical Society. All rights reserved.